Congenital infection with atypical porcine pestivirus (APPV) is associated with disease and viral persistence. (January 2018) - Schwarz, Lukas; Riedel, Christiane; Högler, Sandra; Sinn, Leonie; Voglmayr, Thomas; Wöchtl, Bettina; Dinhopl, Nora; Rebel-Bauder, Barbara; Weissenböck, Herbert; Ladinig, Andrea; Rümenapf, Till; Lamp, Benjamin
Abstract In 2013, several Austrian piglet-producing farms recorded outbreaks of action-related repetitive myoclonia in newborn piglets ("shaking piglets"). Malnutrition was seen in numerous piglets as a complication of this tremor syndrome. Overall piglet mortality was increased and the number of weaned piglets per sow decreased by more than 10% due to this outbreak. Histological examination of the CNS of affected piglets revealed moderate hypomyelination of the white substance in cerebellum and spinal cord. We detected a recently discovered pestivirus, termed atypical porcine pestivirus (APPV) in all these cases by RT-PCR. A genomic sequence and seven partial sequences were determined and revealed a 90% identity to the US APPV sequences and 92% identity to German sequences. In confirmation with previous reports, APPV genomes were identified in different body fluids and tissues including the CNS of diseased piglets. APPV could be isolated from a "shaking piglet", which was incapable of consuming colostrum, and passaged on different porcine cells at very low titers. To assess the antibody response a blocking ELISA was developed targeting NS3. APPV specific antibodies were identified in sows and in PCR positive piglets affected by congenital tremor (CT). APPV genomes were detected continuously in piglets that gradually recovered from CT, while the antibody titers decreased over a 12-week interval, pointing towards maternally transmitted antibodies. High viral loads were detectable by qRT-PCR in saliva and semen of infected young adults indicating a persistent infection.